2021
DOI: 10.1038/s41467-021-22141-z
|View full text |Cite
|
Sign up to set email alerts
|

Covalent organic framework nanofluidic membrane as a platform for highly sensitive bionic thermosensation

Abstract: Thermal sensation, which is the conversion of a temperature stimulus into a biological response, is the basis of the fundamental physiological processes that occur ubiquitously in all organisms from bacteria to mammals. Significant efforts have been devoted to fabricating artificial membranes that can mimic the delicate functions of nature; however, the design of a bionic thermometer remains in its infancy. Herein, we report a nanofluidic membrane based on an ionic covalent organic framework (COF) that is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 57 publications
(60 reference statements)
0
62
0
Order By: Relevance
“…163 Zhang et al reported an iCOF-based nanofluidic membrane that is capable of intelligently monitoring temperature variations and can function as a platform for highly sensitive bionic thermosensation. 282 Zhou et al reported a ferrocene-functionalized COF and further loaded with glutathione peroxidase 4 inhibitor for enhancing chemodynamic therapy via redox dyshomeostasis. 283 These exciting results further expand the biomedical applications and suggest the great potential of POPs for many novel biomedical applications.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…163 Zhang et al reported an iCOF-based nanofluidic membrane that is capable of intelligently monitoring temperature variations and can function as a platform for highly sensitive bionic thermosensation. 282 Zhou et al reported a ferrocene-functionalized COF and further loaded with glutathione peroxidase 4 inhibitor for enhancing chemodynamic therapy via redox dyshomeostasis. 283 These exciting results further expand the biomedical applications and suggest the great potential of POPs for many novel biomedical applications.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…8a). Since the first COF appeared in year 2005 325 , a large number of 2D/3D COFs materials have been designed and synthesized for broad applications in gas storage and separation 326,327 , drug delivery 328,329 , catalysis [330][331][332] , photoelectronic devices 333,334 , supercapacitors 335,336 , and batteries [337][338][339] . Normally, 2D COFs can be prepared through the polycondensation reactions or coupling reactions, and their structures are confirmed through the structural simulation together with the powder X-ray diffraction (PXRD) pattern matching.…”
Section: D Covalent Organic Frameworkmentioning
confidence: 99%
“…Angstrom-sized ion channel devices/membranes were also fabricated by confined growth of zinc nitrate hydroxide and DA18C6-nitrate crystals into single glass nanopores, 132 growth of covalent organic framework membranes on nanoporous supports, 133 and liquid-crystalline nanostructured membranes. 134 Solid confinement conversion methods were developed to fabricate functional and angstrom-porous PSS@CuBTC 135 and DNA@-ZIF-8 136 (Fig.…”
Section: Other Methodsmentioning
confidence: 99%